2018
DOI: 10.1101/451674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crossover recombination and synapsis are linked by adjacent regions within the N terminus of the Zip1 synaptonemal complex protein

Abstract: Accurate chromosome segregation during meiosis relies on the prior establishment of at least one crossover recombination event between homologous chromosomes, which is often associated with the meiosis-specific MutSg complex. The recombination intermediates that give rise to MutSg interhomolog crossovers are embedded within a hallmark meiotic prophase structure called the synaptonemal complex (SC), but the mechanisms that coordinate the processes of SC assembly (synapsis) and crossover recombination remain poo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The SC-CR is dispensable for initial homologous pairing and DSB formation, but when it is absent, meiotic COs are reduced or eliminated (depending on the organism), indicating that SC-CR components play a role in promoting CO formation (for review see: (Hillers et al, 2017;Page and Hawley, 2004)). The SC is a long known cytological hallmark of meiosis (Fawcett, 1956;Moses, 1956) and has been implicated previously in multiple aspects of CO regulation (Hayashi et al, 2010;Libuda et al, 2013;MacQueen et al, 2002;Sym et al, 1993;Sym and Roeder, 1994;Voelkel-Meiman et al, 2016). Further, recent studies have revealed dynamic properties of the SC and have begun to provide insight regarding how changes in SC dynamics might contribute both to nucleus-wide and chromosome-autonomous signaling systems that limit DSBs and inhibit excess COs (Machovina et al, 2016;Nadarajan et al, 2017;Pattabiraman et al, 2017;Rog et al, 2017;Subramanian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The SC-CR is dispensable for initial homologous pairing and DSB formation, but when it is absent, meiotic COs are reduced or eliminated (depending on the organism), indicating that SC-CR components play a role in promoting CO formation (for review see: (Hillers et al, 2017;Page and Hawley, 2004)). The SC is a long known cytological hallmark of meiosis (Fawcett, 1956;Moses, 1956) and has been implicated previously in multiple aspects of CO regulation (Hayashi et al, 2010;Libuda et al, 2013;MacQueen et al, 2002;Sym et al, 1993;Sym and Roeder, 1994;Voelkel-Meiman et al, 2016). Further, recent studies have revealed dynamic properties of the SC and have begun to provide insight regarding how changes in SC dynamics might contribute both to nucleus-wide and chromosome-autonomous signaling systems that limit DSBs and inhibit excess COs (Machovina et al, 2016;Nadarajan et al, 2017;Pattabiraman et al, 2017;Rog et al, 2017;Subramanian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, SC assembly is triggered at recombination sites and is normally coupled to intermediate steps in the recombination process: In zip2, zip3, zip4, spo16, and mer3 mutants, SC fails to assemble from recombination sites, possibly due to a failure to recruit a key SC structural building block (Zip4, for example, which binds directly to Ecm11 (PYATNITSKAYA et al 2022)), or a failure to achieve a particular recombination intermediate capable of triggering SC elaboration. Certain zip1 mutants (including the null) exhibit a combined deficit in crossovers and SC similar to most zmm mutants, but the existence of two classes of zip1 separation-of-function alleles -those that allow SC assembly but not MutSγ crossovers and those that allow MutSγ crossovers but not SC assembly -indicate that Zip1 promotes the two processes of recombination and SC assembly independently, and that Zip1 is likely centrally involved in the mechanism that couples the two processes (VOELKEL-MEIMAN 2018). Precisely what Zip1's procrossover function entails, and how individual ZMM proteins engage with Zip1 in the coordinated processes of recombination and synapsis remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%